Lactobacillus paragasseri HM018 derived from breast milk ameliorates hyperlipidemia in high-cholesterol rats by modulating bile acid metabolism - Yao, Chunyu; Li, Xianping; Tang, Mi; Liu, Lu; Cai, Xiaoqian; Yuan, Xueping; Hu, Jufeng; Zhao, Junying; Qiao, Weicang; Zhang, Yue; Chen, Lijun (Frontiers in Microbiology, 2025)
IntroductionHyperlipidemia, a prevalent metabolic disorder with rising global incidence, has become a major public health concern. Probiotics allow for a mild intervention strategy for hyperlipidemia management that has garnered increasing attention.MethodsIn this study, we investigated the therapeutic effects and underlying mechanisms of Lactobacillus paragasseri HM018 in hypercholesterolemic rats.Results and discussionWe established three dosage groups (2.5 × 108, 5 × 108, and 1.5 × 109 CFU/rat), demonstrating that HM018 significantly reduced high-fat diet-induced serum total cholesterol, triglycerides, and low-density lipoprotein cholesterol levels, while ameliorating gut microbiota dysbiosis and decreasing the Firmicutes/Bacteroidetes ratio. Our transcriptomic analysis revealed that HM018 markedly upregulated Apoa1 expression both in the ileum and liver, while enhancing Abcg5/Abcg8 gene expression to promote β-sitosterol efflux. Concurrently, hepatic Cocs2/3 and Cish gene expression was downregulated, attenuating their inhibitory effects on hormonal and glucagon signaling, thereby improving glucose and lipid metabolism. Metabolomic profiling further indicated that HM018 significantly altered bile acid composition by modulating gut microbiota-mediated bile acid metabolism. In conclusion, Lactobacillus paracasei HM018 could ameliorate hyperlipidemia through multiple pathways, including gut microbiota modulation, hepatic lipid/glucose/bile acid metabolism improvement, and intestinal cholesterol efflux gene expression enhancement.